Ecosystem engineering in the Quaternary of the West Coast of South Africa. Issue 1 (18th February 2021) - Braun, David R.; Faith, John Tyler; Douglass, Matthew J.; Davies, Benjamin; Power, Mitchel J.; Aldeias, Vera; Conard, Nicholas J.; Cutts, Russell; DeSantis, Larisa R. G.; Dupont, Lydie M.; Esteban, Irene; Kandel, Andrew W.; et al.
Abstract: Despite advances in our understanding of the geographic and temporal scope of the Paleolithic record, we know remarkably little about the evolutionary and ecological consequences of changes in human behavior. Recent inquiries suggest that human evolution reflects a long history of interconnections between the behavior of humans and their surrounding ecosystems (e.g., niche construction). Developing expectations to identify such phenomena is remarkably difficult because it requires understanding the multi‐generational impacts of changes in behavior. These long‐term dynamics require insights into the emergent phenomena that alter selective pressures over longer time periods which are not possible to observe, and are also not intuitive based on observations derived from ethnographic time scales. Generative models show promise for probing these potentially unexpected consequences of human‐environment interaction. Changes in the uses of landscapes may have long term implications for the environments that hominins occupied. We explore other potential proxies of behavior and examine how modeling may provide expectations for a variety of phenomena.